SURGICAL TACTICS FOR COMPLICATED FORMS OF CHOLELISTICS IN ELDERLY AND SENILE PATIENTS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
According to researchers, more than half (55-63.8%) of hospitalized patients diagnosed with cholelithiasis have complicated forms of this pathology of varying severity..